Muamalah Fiqh Analysis of the Use of Shopee Paylater: (Case Study on the Shopee Application) - Ahmadi, Mirzam Arqy; Khasanah, Uswatun; Faza, Putri Rizqya; Adelia, Tifani; Satiti, Saltsa Woro Ayu; Agustina, Alya; Pratama, Shaka Yudha; Fanny, Dhevan Muhammad (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2024)
In the era of advancing technology, online services have become a solution to meet human needs by facilitating access to various aspects of life. One renowned online shopping platform is Shopee, Providing an extensive array of items, ranging from food and apparel to household appliances.. Shopee users are familiar with the